OPS3 - Progressing toward Environmental Results : Third Overall Performance Study of the Global Environmental Facility, Executive Version - Global Environment Facility (Washington, DC: Global Environment Facility, 2012)
The purpose of the Third Overall Performance Study (OPS3), commissioned by the Global Environment Facility (GEF) Council, is "to assess the extent to which GEF has achieved, or is on its way towards achieving its main objectives, as laid down in the GEF Instrument and subsequent decisions by the GEF Council and the Assembly, including key documents such as the Operational Strategy and the Policy Recommendations agreed as part of the Third Replenishment of the GEF Trust Fund." (GEF/C.23/4) The OPS3 team recognizes that this study is taking place at a critical time and will provide input that is relevant to the Fourth Replenishment of the GEF Trust Fund, which will be taking place shortly after the publication of the OPS3 study. A primary goal of OPS3 is to provide relevant, timely, and actionable recommendations for each of the Terms of Reference (TOR) areas to support the replenishment process and associated programming. The scope of OPS3 is defined by the "Terms of Reference for the Third Overall Performance Study approved by the GEF Council on May 21, 2004, and it covers five main themes : 1) Results of GEF activities. 2) Sustainability of results at the country level. 3) GEF as a catalytic institution. 4) GEF policies, institutional structure, and partnerships. 5) GEF implementation processes.